A population genomics insight by 2b‐RAD reveals populations' uniqueness along the Italian coastline in Leptopsammia pruvoti (Scleractinia, Dendrophylliidae). Issue 7 (11th April 2019) - Boscari, Elisa; Abbiati, Marco; Badalamenti, Fabio; Bavestrello, Giorgio; Benedetti‐Cecchi, Lisandro; Cannas, Rita; Cau, Angelo; Cerrano, Carlo; Chimienti, Giovanni; Costantini, Federica; Fraschetti, Simonetta; Ingrosso, Gianmarco; et al.
Abstract: Aim: Marine bioconstructions such as coralligenous formations are hotspot of biodiversity and play a relevant ecological role in the preservation of biodiversity by providing carbon regulation, protection and nursery areas for several marine species. For this reason, the European Union Habitat Directive included them among priority habitats to be preserved. Although their ecological role is well established, connectivity patterns are still poorly investigated, representing a limit in conservation planning. The present study pioneers a novel approach for the analysis of connectivity in marine bioconstructor species, which often lack suitable genetic markers, by taking advantage of next‐generation sequencing techniques. We assess the geographical patterns of genomic variation of the sunset cup coral Leptopsammia pruvoti Lacaze‐Duthiers, 1897, an ahermatypic, non‐zooxanthellate and solitary scleractinian coral species common in coralligenous habitats and distributed across the Mediterranean Sea. Location: The Italian coastline (Western and Central Mediterranean). Methods: We applied the restriction site‐associated 2b‐RAD approach to genotype over 1, 000 high‐quality and filtered single nucleotide polymorphisms in 10 population samples. Results: The results revealed the existence of a strongly supported genetic structure, with highly significant pairwise F ST values between all the population samples, including those collected about 5 km apart from each other. Moreover, genomic data indicate that the strongest barriers to gene flow are between the western (Ligurian–Tyrrhenian Sea) and the eastern side (Adriatic Sea) of the Italian peninsula. Main conclusions: The strong differentiation found in L. pruvoti is similar to that found in other species of marine bioconstructors investigated in this area, but it strongly contrasts with the small differences found in many fish and invertebrates at the same geographical scale. All in one, our results highlight the importance of assessing connectivity in species belonging to coralligenous habitats as, due to their limited dispersal ability, they might require specific spatial conservation measures.